1991
DOI: 10.1002/j.1556-6676.1991.tb02644.x
|View full text |Cite
|
Sign up to set email alerts
|

The Minnesota Multiphasic Personality Inventory‐2: A Review

Abstract: The new version of the Minnesota Multiphasic Personality

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…Many respondents to the MMPI in recent years have been forced to ask examiners the meaning of such terms as drop the handkerchief (Duckworth, 1991a). Others have commented on the questions relating to religious beliefs and preferences and deportment in school or have puzzled over the meaning of other items (see Greene, 1991, p. 23, for illustrations).…”
Section: Minor Problemsmentioning
confidence: 99%
“…Many respondents to the MMPI in recent years have been forced to ask examiners the meaning of such terms as drop the handkerchief (Duckworth, 1991a). Others have commented on the questions relating to religious beliefs and preferences and deportment in school or have puzzled over the meaning of other items (see Greene, 1991, p. 23, for illustrations).…”
Section: Minor Problemsmentioning
confidence: 99%
“…Construction of the PAI was intended to provide a superior alternative to the MMPI-2 instrument (Butcher, Dahlstrom, Graham, Tellegen, & Kaemmer, 1989), in view of the latter's well-documented psychometric limitations (e.g., Caldwell, 1991;Duckworth, 1991;Eysenck, 1991;Helmes & Reddon, 1993). According to White (1993, p. 23), "When compared with the MMPI-2, the PAI has a number of significant advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Duckworth (1991a) reported that the MMPI-2 does not have any available validity data for the PK scale. Duckworth (1991b) and Caldwell (1991) cautioned against assuming that profiles from the MMPI-2 and the orig-inal MMPI are similar because comparisons between the MMPI and MMPI-2 are still under research investigation. Graham (1990) reported an internal consistency for the PK scale of the MMPI-2 for males and females for normative samples of .85 and .87, respectively.…”
Section: Employing the Minnesota Multiphasic Personality Inventory~mmmentioning
confidence: 99%